Ultra-white diamond glazed tile with reduced crack defects and preparation method thereof

By optimizing the brick composition and preparation process of ultra-white diamond glazed tiles, the problems of crack center and edge crack defects during firing are solved, and the effect of improving production quality and stability is achieved.

CN117776697BActive Publication Date: 2025-04-15HEYUAN DONGYUAN EAGLE CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311822247.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-27
Publication Date
2025-04-15
Estimated Expiration
2043-12-27

AI Technical Summary

Technical Problem

Existing ultra-white diamond glazed tiles are prone to cracking and edge cracking defects during firing, which affects production quality and output.

Method used

By optimizing the composition and preparation process of brick blanks, the use of high-white pellet soil, medium-white pellet soil and bentonite is increased, the role of modified kaolin and cherry in the base glaze, and the role of ultra-white zirconium silicate in the surface glaze, the moisture content and firing temperature are regulated, and the temperature rise and cooling rate during the firing process are controlled.

Benefits of technology

It effectively reduces the shrinkage and deformation of brick blanks during sintering, reduces the risk of edge cracks and cracks, and improves the production quality and stability of products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004634320800000131
    Figure BDA0004634320800000131
Patent Text Reader

Abstract

The invention discloses an ultra-white diamond glazed tile with reduced crack defects and a preparation method thereof, comprising the following steps: putting mixed raw materials into a ball mill for ball milling to obtain ball milling slurry; atomizing the ball milling slurry under pressure into droplets, drying the ball milling slurry into powder by spraying, then pressing and molding, and treating the brick with a base glaze, printing inkjet patterns on the surface of the base glaze layer, applying a top glaze after water wetting, and placing the brick in a roller kiln for firing; the high-white ball clay and medium-white ball clay contained in the brick components of the invention have fine particles and high plasticity, can fill tiny gaps and defects in the brick, and make the brick more dense and uniform; bentonite can expand into a colloidal substance when in contact with water, can increase the plasticity and plasticity of the brick, and make it easier to mold and keep its shape; by adjusting the particle grading, particles of different particle sizes can better fill the gaps, thereby forming a denser brick structure, and greatly reducing the defects of cracks and side cracks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic tiles, and in particular to an ultra-white diamond glazed tile with reduced crack defects and a preparation method thereof. Background Art

[0002] Ceramic tiles are a kind of material that can be used as floor decoration, sometimes also called floor tiles. They are made of clay and have various specifications. They are hard, pressure-resistant, wear-resistant, and moisture-proof. Some are glazed and have decorative effects. They are mostly used for the ground and floors of public and civil buildings. There are many varieties of floor tiles, and there is a lot of room for choice. According to the material, they can be divided into glazed tiles, full-body tiles, polished tiles, vitrified tiles, etc. Ceramic tiles, as a large-area paved floor material, use their own color and texture to create a different style of living environment;

[0003] Super white diamond glazed tile is a high-end tile product with high whiteness, high hardness and smooth glaze. It is popular among consumers for its bright color and good decorative effect. It is widely used in the fields of decoration and construction, and can bring high texture and beautiful effect to the space.

[0004] However, the ultra-white diamond glazed tiles in the prior art are often prone to defects such as cracks in the center and cracks on the edges during the firing process, thereby affecting the production quality and output of the products.

[0005] Therefore, the prior art has defects and needs to be improved. Summary of the invention

[0006] The technical problem to be solved by the present invention is to provide an ultra-white diamond glazed tile with reduced crack defects and improved production quality of the tile, and a preparation method thereof.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] A method for preparing an ultra-white diamond glazed tile with reduced crack defects comprises the following steps:

[0009] S1. Mix the raw materials of the bricks according to a certain weight ratio to obtain a mixed raw material; then put the mixed raw material into a ball mill for ball milling; control the moisture content to 33-36%, the fineness to 0.6-0.8%, the specific gravity to 1.55-1.65 g / ml, and the flow rate to 35-65 s to obtain a ball mill slurry;

[0010] The brick blank is composed of the following components by weight: potassium sodium sand: 40-55 parts, potassium sand: 10-15 parts, high white ball clay: 3-5 parts, medium white ball clay: 14-20 parts, bentonite: 4-8 parts, superplastic clay: 5-8 parts, bauxite: 1-2 parts, black clay: 0-2 parts, talcum particles: 2-4 parts, brightener: 0.2-1 parts, debonding agent: 0.4-0.8 parts, water glass: 0.3-0.7 parts, and reinforcing agent 0.1-0.3 parts;

[0011] S2, the ball mill slurry is filtered through an 80-mesh sieve to filter out coarse particles and wood residue impurities, and then iron is removed, and then the ball mill slurry is pressurized to be atomized into droplets, and then spray dried into powder; wherein the moisture content of the powder is controlled at 7-7.5%, and the particle size distribution is: 40-mesh sieve upper material> 68%, 100-mesh sieve lower material< 5%;

[0012] S3, applying the powder to a mold to obtain a green body, and pressing the green body through a press to obtain a brick body, wherein the thickness of the brick body is 11.5-12 mm;

[0013] S4, placing the bricks in a drying kiln and drying them at 140-250°C to make the moisture content in the bricks less than 0.7% of the total mass;

[0014] S5. The dried bricks are glazed with a bell glaze sprayer, and the glaze amount is 110-120g / m 2 , to obtain the base glaze layer;

[0015] S6, inkjet pattern printing is performed on the surface of the base glaze layer to obtain a pattern layer, and then after drying at 85-95°C, the surface of the pattern layer is coated with a 12-18g / m 2 Wet with water, then press 170-200g / m 2 applying a top glaze to obtain a top glaze layer;

[0016] S7. Place the brick blank prepared in step S6 into a drying kiln for drying at a drying temperature of 170°C, and then send it into a roller kiln for firing at a firing temperature of 1190-1230°C for 50-60 minutes, thereby obtaining an ultra-white diamond glazed tile with reduced crack defects, which is provided with a brick blank, a base glaze layer, a pattern layer and a surface glaze layer from bottom to top.

[0017] Using the above technical solution, in step S5, the base glaze is composed of the following components by weight: potassium feldspar: 15-20 parts, sodium feldspar: 24-32 parts, silica sand powder: 38-42 parts, modified kaolin: 12-14 parts, burned talc: 12-16 parts, nepheline: 4-12 parts and aluminum oxide: 2-3 parts.

[0018] Using the above technical solution, in step S6, the glaze is composed of the following components by weight: white stone powder: 30-38 parts, ultra-white zirconium silicate: 8-12 parts, calcite: 4-8 parts, calcite: 22-26 parts, quartz: 4-6 parts, aluminum oxide: 1-2 parts and titanium oxide: 0.1-0.6 parts.

[0019] Using the above technical solution, in step S1, 1.2 wt% sodium tripolyphosphate and 0.7 wt% carboxymethyl cellulose are added to the mixed raw materials during the ball milling process for co-ball milling, and the ball milling time is 4-8 hours.

[0020] Using the above technical scheme, the preparation process of the modified kaolin is: add kaolin, triethanolamine, solvent water and urea in a mass ratio of 14:3:36:5 into a ball mill for ball milling for 20-40 minutes, the ball mill speed is: 400-480r / min, the slurry is left to stand for 24 hours after leaving the mill, and then dehydrated and dried for standby use.

[0021] Using the above technical solution, in step S3, the pressure of the press is 2800 KN, and the thickness of the green body is controlled to be 13-14 mm.

[0022] By adopting the above technical solution, in step S7, the moisture content of the bricks in the drying kiln is controlled to be 0.3%.

[0023] Using the above technical solution, in step S7, the firing stages of the bricks in the roller kiln include: dehumidification at 170-280°C, preheating and drying at 280-680°C, oxidation and decomposition at 680-1190°C, vitrification firing at 1190-1230°C, foaming and expansion at 1230-1280°C, rapid cooling at 1280-680°C, medium-speed cooling at 680-280°C and slow cooling at 280-55°C.

[0024] By adopting the above technical scheme, in the preheating and drying stage, the temperature rise rate is 40-50℃ / min; in the oxidation and decomposition stage, the temperature rise rate is 20-30℃ / min; in the rapid cooling stage, the temperature drop rate is 80-90℃ / min; in the medium-speed cooling stage, the temperature drop rate is 35-45℃ / min; in the slow cooling stage, the temperature drop rate is 15-20℃ / min.

[0025] The present invention also provides an ultra-white diamond glazed tile with reduced crack center defects, which is prepared by the method for preparing the ultra-white diamond glazed tile with reduced crack center defects described in any of the above technical solutions.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The brick blank components of the present invention contain high white ball clay, medium white ball clay and bentonite. The high white ball clay and medium white ball clay have fine particles and high plasticity, can fill tiny gaps and defects in the brick blank, make the brick blank more dense and uniform, thereby reducing the shrinkage and deformation of the brick blank during the sintering process, and reducing the risk of edge cracks and core cracks in the brick blank; bentonite has high water absorption and expansion, can expand into a colloidal substance when in contact with water, can increase the plasticity and plasticity of the brick blank, make it easier to shape and keep the shape, and not easy to crack; and in the process of atomizing and drying the powder, by adjusting the particle grading, particles of different particle sizes can better fill the gaps, thereby forming a denser brick blank structure; the components of the base glaze contain modified kaolin and nepheline, the modified kaolin can increase the viscosity and adhesion of the base glaze, improve the adhesion and covering of the base glaze, and when the base glaze is attached to When the base glaze is applied to the surface of the brick blank, the viscosity of the modified kaolin can help the base glaze to better combine with the brick blank to form a uniform coating; the role of nepheline in the base glaze is to increase the fluidity and adhesion of the base glaze. When the base glaze flows to the surface of the brick blank, nepheline can improve the meltability and wettability of the base glaze, making it easier to cover the surface of the brick blank and form a uniform coating, and the glaze layer is not prone to cracking; in the top glaze, ultra-white zirconium silicate, as a high-purity silicate mineral, has high whiteness and gloss. Ultra-white zirconium silicate can increase the gloss and transparency of the top glaze, making it more beautiful, and can also improve the adhesion and wear resistance of the top glaze, reduce stress concentration on the surface of the brick blank, thereby reducing the risk of edge cracks and cracks; in the preparation process, by strictly controlling the moisture content of the brick blank at each step, the brick blank can gradually lose moisture during the drying process, thereby improving the stability of the brick blank and reducing the internal stress of the brick blank. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0029] The present invention provides a method for preparing ultra-white diamond glazed tiles with reduced crack defects.

[0030] The following steps are involved:

[0031] S1. Mix the raw materials of the green bricks according to a certain weight proportion to obtain a mixed raw material; then put the mixed raw material into a ball mill for ball milling; control the water content to 33-36%, the fineness to 0.6-0.8%, the specific gravity to 1.55-1.65g / ml, and the flow rate to 35-65s to obtain a ball milling slurry; the fineness refers to the particle size of the particles in the ball milling slurry. The appropriate fineness can increase the ball milling surface area of ​​the green brick raw materials, thereby improving the ball milling efficiency, facilitating the uniform dispersion and mixing of the particles, thereby reducing the concentration and uneven distribution of stress inside the green bricks, and reducing the possibility of cracking the center and edge of the green bricks during the sintering process;

[0032] The brick blank is composed of the following components by weight: potassium sodium sand: 40-55 parts, potassium sand: 10-15 parts, high white ball clay: 3-5 parts, medium white ball clay: 14-20 parts, bentonite: 4-8 parts, super plastic clay: 5-8 parts, bauxite: 1-2 parts, black clay: 0-2 parts, talcum particles: 2-4 parts, brightener: 0.2-1 parts, debonding agent: 0.4-0.8 parts, water glass: 0.3-0.7 parts, and reinforcing agent 0.1-0.3 parts; high white ball clay and medium white ball clay are used as fillers and reinforcing agents. They have fine particles and high plasticity and can fill tiny gaps and defects in the brick blank. , making the brick more dense and uniform, thereby reducing the shrinkage and deformation of the brick during the sintering process, and reducing the risk of edge cracks and cracks in the brick; bentonite has high water absorption and expansion, and can expand into a colloidal substance when in contact with water. In the process of brick preparation, bentonite can increase the plasticity and plasticity of the brick, making it easier to shape and maintain its shape; the debonding agent has adhesive properties, which can increase the adhesive force and plasticity of the brick, so that the brick maintains the stability of its shape and structure; water glass, as a binder, can provide adhesive force and strength for the brick, increase the bonding effect between brick particles, and avoid cracking. The reinforcing agent can increase the strength and durability of the brick;

[0033] S2, the ball mill slurry is filtered through an 80-mesh sieve to remove coarse particles and wood residue impurities, and then iron is removed, and then the ball mill slurry is pressurized to be atomized into droplets, and then spray dried into powder; wherein, the moisture content of the powder is controlled at 7-7.5%, and the particle gradation is: 40-mesh sieve upper material> 68%, 100-mesh sieve lower material< 5%; the appropriate moisture content can provide fluidity and plasticity for the brick blank during the preparation process. When the moisture content of the powder is moderate, it can flow and fill better in the mold, making the molding of the brick blank more uniform and stable, so as to form a denser brick blank; and during the mold pressing process, the water content The particles can act as lubricants to better combine the powder particles and fill the pores, thereby improving the density and strength of the brick, thereby reducing the risk of edge cracks and core cracks; the 40-mesh sieve upper material > 68% means that the proportion of particles in the powder with a particle size larger than the 40-mesh sieve aperture is greater than 68%, and the 100-mesh sieve lower material < 5% means that the proportion of particles in the powder with a particle size smaller than the 100-mesh sieve aperture is less than 5%; the particle grading setting can improve the density and uniformity of the brick, so that particles of different particle sizes can better fill the gaps, thereby forming a denser brick structure.

[0034] S3, applying the powder to a mold to obtain a green body, and pressing the green body through a press to obtain a brick body, wherein the thickness of the brick body is 11.5-12 mm;

[0035] S4. Place the bricks in a drying kiln and dry them at 140-250°C to reduce the moisture content in the bricks to less than 0.7% of the total mass. By drying and evaporating the moisture inside the bricks, the moisture gradient inside and outside the bricks can be reduced. A smaller moisture gradient can reduce the shrinkage difference of the bricks during the drying and sintering process, thereby reducing the risk of edge cracks and core cracks.

[0036] S5. The dried bricks are glazed with a bell glaze sprayer, and the glaze amount is 110-120g / m 2 , to obtain the base glaze layer; the base glaze layer can form a protective coating covering the surface of the brick, which can prevent the penetration and loss of water, reduce the moisture difference between the surface of the brick and the environment, and thus protect the surface of the brick from erosion and damage by external factors, such as oxidation, corrosion, pollution, etc.; the base glaze will be ceramicized during the sintering process to form a dense ceramic film. This ceramic film can increase the strength and stability of the brick, making it more wear-resistant, pressure-resistant and chemically resistant.

[0037] S6, inkjet pattern printing is performed on the surface of the base glaze layer to obtain a pattern layer, and then after drying at 85-95°C, the surface of the pattern layer is coated with a 12-18g / m 2 Wet with water, then press 170-200g / m 2Apply the glaze to obtain the glaze layer; drying is to evaporate the water in the inkjet pattern layer to ensure the clarity and stability of the inkjet pattern; watering can make the surface of the pattern layer fully moist, increase the contact area between the glaze and the pattern layer, facilitate the uniform coverage and flow of the glaze, promote the adhesion of the glaze, and enable the glaze layer to better adhere to the pattern layer; it should be noted that too little water may not be able to fully moisten the surface of the pattern layer, resulting in insufficient or uneven adhesion of the glaze; while too much water will cause the glaze to be overly diluted, the fluidity is too strong, and it is difficult to control the uniformity of glazing; the glaze layer can provide a protective coating for the surface of the brick to prevent water penetration and erosion by external factors. At the same time, the glaze can give the brick a rich color, texture and texture, increase the decorative effect of the product, and enhance the ornamental and aesthetic qualities.

[0038] S7. Place the brick blank prepared in step S6 into a drying kiln for drying at a drying temperature of 170°C, and then send it to a roller kiln for firing at a firing temperature of 1190-1230°C and a firing time of 50-60min, thereby obtaining an ultra-white diamond glazed tile with reduced crack defects, which is provided with a brick blank, a bottom glaze layer, a pattern layer and a surface glaze layer from bottom to top. The high temperature during the drying process can promote physical and chemical reactions in the brick blank, and is helpful for pre-firing and pre-baking. Pre-firing refers to the pyrolysis and volatilization of organic matter and moisture in the brick blank at a relatively low temperature, eliminating the residue of organic matter and the evaporation of moisture. Pre-baking refers to the process of evenly evaporating the moisture in the brick blank through appropriate temperature and time during the drying process to achieve a certain degree of dryness. Pre-firing and pre-baking can eliminate volatile substances in the brick blank in advance and reduce the risk of bubbles and cracking during the firing process.

[0039] Further, in step S5, the base glaze is composed of the following components by weight: potassium feldspar: 15-20 parts, sodium feldspar: 24-32 parts, silica sand powder: 38-42 parts, modified kaolin: 12-14 parts, calcined talc: 12-16 parts, nepheline: 4-12 parts and alumina: 2-3 parts. The modified kaolin can increase the viscosity and adhesion of the base glaze, improve the adhesion and coverage of the base glaze, and when the base glaze is attached to the surface of the brick, the viscosity of the modified kaolin can help the base glaze to better combine with the brick to form a uniform coating; the role of nepheline in the base glaze is to increase the fluidity and adhesion of the base glaze. When the base glaze flows to the surface of the brick, the nepheline can improve the fusibility and wettability of the base glaze, making it easier to cover the surface of the brick and form a uniform coating.

[0040] Further, in step S6, the glaze is composed of the following components by weight: white stone powder: 30-38 parts, ultra-white zirconium silicate: 8-12 parts, calcite: 4-8 parts, calcite: 22-26 parts, quartz: 4-6 parts, aluminum oxide: 1-2 parts and titanium oxide: 0.1-0.6 parts. White stone powder is an inorganic substance, the main component of which is calcium carbonate. Its role in the glaze is to increase the gloss and smoothness of the glaze and improve the touch and texture of the glaze; ultra-white zirconium silicate is a high-purity silicate mineral with high whiteness and gloss. In the glaze, ultra-white zirconium silicate can increase the gloss and transparency of the glaze, making it more beautiful. It can also improve the adhesion and wear resistance of the glaze, reduce the stress concentration on the surface of the brick, and thus reduce the risk of edge cracks and cracks; titanium oxide has high whiteness and hiding power, which can increase the hiding power and whiteness of the glaze, making it more uniform and beautiful.

[0041] Furthermore, in step S1, during the ball milling process, 1.2 wt% of sodium tripolyphosphate and 0.7 wt% of carboxymethyl cellulose are added to the mixed raw materials for joint ball milling, and the ball milling time is 4-8 hours; sodium tripolyphosphate has good dispersibility and wettability. During the ball milling process, sodium tripolyphosphate can be used as a dispersant and wetting agent to help the particles in the mixed raw materials to be better dispersed in the ball milling slurry and fully contact and mix with other components; carboxymethyl cellulose has good dispersibility and adhesion. During the ball milling process, carboxymethyl cellulose can be used as a dispersant and adhesive to help improve the uniformity and stability of the mixed raw materials.

[0042] Furthermore, the preparation process of the modified kaolin is as follows: kaolin, triethanolamine, solvent water and urea are added to a ball mill in a mass ratio of 14:3:36:5 for ball milling for 20-40 minutes, the ball milling speed is 400-480r / min, the slurry is left to stand for 24 hours after exiting the mill, and is then dehydrated and dried for standby use. Urea is an organic compound that mainly acts as a thickener in the preparation process of modified kaolin. Urea can increase the viscosity of the slurry, making it have better fluidity and adhesion during the ball milling process; triethanolamine has surface activity and dispersibility. During the modification process, triethanolamine can be used as a dispersant and surfactant to reduce the adsorption and aggregation forces between particles, so that the particles can be better dispersed in the solvent water and mixed evenly with other components; triethanolamine and urea interact with kaolin particles, change the properties of the surface of kaolin particles, and increase the hydrophilicity and dispersibility of kaolin; the modified kaolin particles are evenly dispersed, which can provide better support and filling effects during the preparation of bricks, thereby enhancing the structural stability of the bricks.

[0043] Further, in step S3, the pressure of the press is 2800 KN, and the thickness of the green brick is controlled to be 13-14 mm. By setting the pressure of the press to 2800 KN, it is ensured that sufficient pressure is applied to compact the powder during the pressing process. Appropriate pressure can ensure that the particles inside the brick are tightly bound and reduce the presence of voids and pores.

[0044] Further, in step S7, the moisture content of the bricks in the drying kiln is controlled to be 0.3%. By controlling the moisture content of the bricks, the bricks can gradually lose moisture during the drying process, thereby improving the stability of the bricks. The lower moisture content can reduce the volume change of the bricks caused by water evaporation during the firing process, reduce the stress of the bricks, and reduce the risk of edge cracks and cracks.

[0045] Further, in step S7, the firing stage of the brick in the roller kiln includes: dehumidification at 170-280°C. At this stage, the temperature in the kiln gradually increases, which is conducive to the evaporation and removal of moisture inside the brick. By gradually reducing the moisture content of the brick, the internal stress generated during the evaporation of moisture can be reduced; preheating and drying at 280-680°C. At this stage, the brick is further heated to remove residual moisture and volatile substances. Appropriate preheating and drying can make the temperature and humidity inside the brick uniformly distributed, reducing the temperature and humidity gradient during sintering; oxidation and decomposition at 680-1190°C. At this stage, the organic matter in the brick begins to oxidize and decompose, releasing gas and other volatile substances. This process helps to stabilize the structure of the brick and reduce the accumulation of internal stress; vitrification firing at 1190-1230°C, At this stage, the bricks gradually reach the vitrification temperature, and the brick particles begin to melt and combine, which helps to further enhance the structural stability of the bricks and reduce the generation of internal stress; foaming expansion 1230-1280℃, at this stage, the gas in the bricks begins to expand, forming pores and air holes, which helps to release internal stress and reduce the internal pressure of the bricks; rapid cooling 1280-680℃, medium cooling 680-280℃ and slow cooling 280-55℃, cooling in different temperature ranges, including rapid cooling, medium cooling and slow cooling. The appropriate cooling process can control the temperature reduction rate of the bricks and avoid thermal stress caused by too rapid cooling; through the settings of the above firing stages, the temperature and humidity changes of the bricks can be controlled, thereby gradually releasing internal stress and reducing the risk of edge cracks and core cracks.

[0046] Furthermore, in the preheating and drying stage, the temperature rise rate is 40-50℃ / min; in the oxidation and decomposition stage, the temperature rise rate is 20-30℃ / min; in the rapid cooling stage, the temperature drop rate is 80-90℃ / min; in the medium-speed cooling stage, the temperature drop rate is 35-45℃ / min; in the slow cooling stage, the temperature drop rate is 15-20℃ / min; in the preheating and drying stage, the moisture in the bricks needs to be evaporated and removed, and a faster temperature rise rate helps to quickly heat the bricks to a higher temperature and promote the evaporation and removal of moisture; in the oxidation and decomposition stage, the organic matter in the bricks begins to oxidatively decompose, releasing gases and other volatile substances. A slower temperature rise rate helps to control the decomposition and oxidation reactions of organic matter, avoid the rapid release of gases and volatile substances caused by too fast a temperature rise rate, and reduce the accumulation of internal stress; in the cooling stage, an appropriate temperature drop rate helps to control the temperature drop rate of the bricks and avoid thermal stress caused by too fast cooling; specifically, the faster temperature drop rate in the rapid cooling stage helps to quickly cool the bricks to a lower temperature and avoid the generation of excessive thermal stress in the bricks; the moderate temperature drop rate in the medium-speed cooling stage helps to further stabilize the temperature and structure of the bricks; the slower temperature drop rate in the slow cooling stage can gradually cool the bricks, reduce the temperature gradient, and help to further release internal stress.

[0047] The present invention also provides an ultra-white diamond glazed tile with reduced crack center defects, which is prepared by the preparation method of the ultra-white diamond glazed tile with reduced crack center defects described in the above technical solution.

[0048] Example 1

[0049] Embodiment 1 of the present invention provides a method for preparing ultra-white diamond glazed tiles with reduced crack defects.

[0050] The following steps are involved:

[0051] S1. Mix the raw materials of the bricks according to a certain weight ratio to obtain a mixed raw material; then put the mixed raw material into a ball mill for ball milling; control the moisture content to 36%, the fineness to 0.8%, the specific gravity to 1.65 g / ml, and the flow rate to 35 s to obtain a ball mill slurry;

[0052] During the ball milling process, 1.2 wt % of sodium tripolyphosphate and 0.7 wt % of carboxymethyl cellulose were added to the mixed raw materials for joint ball milling, and the ball milling time was 4 hours.

[0053] The brick is composed of the following components by weight: 55 parts of potassium sodium sand, 10 parts of potassium sand, 5 parts of high white ball clay, 120 parts of medium white ball clay, 4 parts of bentonite, 5 parts of superplasticized clay, 1 part of bauxite, 2 parts of talc particles, 0.2 parts of brightener, 0.4 parts of debonding agent, 0.7 parts of water glass, and 0.1 parts of reinforcing agent;

[0054] S2, the ball mill slurry is filtered through an 80-mesh sieve to filter out coarse particles and wood residue impurities, and then iron is removed, and then the ball mill slurry is pressurized to be atomized into droplets, and then spray dried into powder; wherein the moisture content of the powder is controlled at 7%, and the particle size distribution is: 40-mesh sieve upper material> 68%, 100-mesh sieve lower material< 5%;

[0055] S3. Apply the powder to a mold to obtain a green body, and press it through a press to obtain a brick body, wherein the thickness of the brick body is 12 mm; the pressure of the press is 2800 KN, and the thickness of the green body is 14 mm.

[0056] S4, placing the bricks in a drying kiln and drying them at 140°C to make the moisture content in the bricks less than 0.7% of the total mass;

[0057] S5. The dried bricks are glazed with a bell glaze sprayer, and the glaze amount is 120g / m 2 , to obtain the base glaze layer;

[0058] The base glaze is composed of the following components by weight: potassium feldspar: 15 parts, sodium feldspar: 32 parts, silica sand powder: 42 parts, modified kaolin: 14 parts, calcined talc: 12 parts, nepheline: 12 parts and aluminum oxide: 2 parts;

[0059] The preparation process of the modified kaolin is as follows: kaolin, triethanolamine, solvent water and urea are added into a ball mill in a mass ratio of 14:3:36:5 for ball milling for 20 minutes at a ball milling speed of 480 r / min. The slurry is allowed to stand for 24 hours after exiting the mill and then dehydrated and dried for standby use.

[0060] S6, inkjet printing is performed on the surface of the base glaze layer to obtain a pattern layer, and then after drying at 85°C, the surface of the pattern layer is coated with 18g / m 2 Wet with water, then press 170g / m 2 applying a top glaze to obtain a top glaze layer;

[0061] The glaze is composed of the following components by weight: 38 parts of white stone powder, 12 parts of ultra-white zirconium silicate, 4 parts of calcite, 22 parts of calcined talc, 4 parts of quartz, 2 parts of aluminum oxide and 0.1 parts of titanium oxide.

[0062] S7. Place the bricks prepared in step S6 into a drying kiln for drying at a drying temperature of 170°C. Control the moisture content of the bricks in the drying kiln to be 0.3%. Then send them into a roller kiln for firing at a firing temperature of 1200°C for 50 minutes to obtain ultra-white diamond glazed tiles with reduced crack defects, which are provided with a brick, a base glaze layer, a pattern layer and a surface glaze layer from bottom to top.

[0063] The firing stages of the bricks in the roller kiln include: dehumidification at 170-280°C, preheating and drying at 280-680°C, oxidation and decomposition at 680-1200°C, vitrification firing at 1200°C, foaming and expansion at 1200-1280°C, rapid cooling at 1280-680°C, medium-speed cooling at 680-280°C and slow cooling at 280-55°C.

[0064] In the preheating and drying stage, the temperature rise rate is 40℃ / min; in the oxidation and decomposition stage, the temperature rise rate is 30℃ / min; in the rapid cooling stage, the temperature drop rate is 80℃ / min; in the medium-speed cooling stage, the temperature drop rate is 35℃ / min; in the slow cooling stage, the temperature drop rate is 15℃ / min.

[0065] Example 2

[0066] Embodiment 1 of the present invention provides a method for preparing ultra-white diamond glazed tiles with reduced crack defects.

[0067] The following steps are involved:

[0068] S1. Mix the raw materials of the bricks according to a certain weight ratio to obtain a mixed raw material; then put the mixed raw material into a ball mill for ball milling; control the moisture content to 33%, the fineness to 0.6%, the specific gravity to 1.55 g / ml, and the flow rate to 65 s to obtain a ball mill slurry;

[0069] During the ball milling process, 1.2 wt % of sodium tripolyphosphate and 0.7 wt % of carboxymethyl cellulose were added to the mixed raw materials for joint ball milling, and the ball milling time was 8 hours.

[0070] The brick blank is composed of the following components by weight: potassium sodium sand: 55 parts, potassium sand: 10 parts, high white ball clay: 3 parts, medium white ball clay: 14 parts, bentonite: 4 parts, superplastic clay: 5 parts, bauxite: 1 part, black clay: 2 parts, talcum particles: 4 parts, brightener: 01 parts, debonding agent: 0.4 parts, water glass: 0.7 parts, and reinforcing agent 0.3 parts;

[0071] S2, the ball mill slurry is filtered through an 80-mesh sieve to filter out coarse particles and wood residue impurities, and then iron is removed, and then the ball mill slurry is pressurized to be atomized into droplets, and then spray dried into powder; wherein the moisture content of the powder is controlled at 7.5%, and the particle size distribution is: 40-mesh sieve upper material> 68%, 100-mesh sieve lower material< 5%;

[0072] S3. Apply the powder to a mold to obtain a green body, and press it through a press to obtain a brick body, wherein the thickness of the brick body is 11.5 mm; the pressure of the press is 2800 KN, and the thickness of the green body is 13 mm.

[0073] S4, placing the bricks in a drying kiln and drying them at 250°C to make the moisture content in the bricks less than 0.7% of the total mass;

[0074] S5. The dried bricks are glazed with a bell glaze sprayer, and the glaze amount is 110g / m 2 , to obtain the base glaze layer;

[0075] The base glaze is composed of the following components by weight: potassium feldspar: 20 parts, sodium feldspar: 24 parts, silica sand powder: 38 parts, modified kaolin: 12 parts, calcined talc: 12 parts, nepheline: 4 parts and aluminum oxide: 3 parts;

[0076] The preparation process of the modified kaolin is as follows: kaolin, triethanolamine, solvent water and urea are added into a ball mill in a mass ratio of 14:3:36:5 for ball milling for 40 minutes at a ball milling speed of 400 r / min. The slurry is allowed to stand for 24 hours after exiting the mill and then dehydrated and dried for standby use.

[0077] S6, inkjet printing is performed on the surface of the base glaze layer to obtain a pattern layer, and then after drying at 95°C, the surface of the pattern layer is coated with a 12g / m 2 Wet with water, then press 200g / m 2 applying a top glaze to obtain a top glaze layer;

[0078] The glaze is composed of the following components by weight: 38 parts of white stone powder, 8 parts of ultra-white zirconium silicate, 4 parts of calcite, 22 parts of calcite, 6 parts of quartz, 2 parts of aluminum oxide and 0.6 parts of titanium oxide.

[0079] S7. Place the bricks prepared in step S6 into a drying kiln for drying at a drying temperature of 170°C. Control the moisture content of the bricks in the drying kiln to be 0.3%. Then send them into a roller kiln for firing at a firing temperature of 1190°C for 60 minutes to obtain ultra-white diamond glazed tiles with reduced crack defects, which are provided with a brick, a base glaze layer, a pattern layer and a surface glaze layer from bottom to top.

[0080] The firing stages of the bricks in the roller kiln include: dehumidification at 170-280°C, preheating and drying at 280-680°C, oxidation and decomposition at 680-1190°C, vitrification firing at 1190°C, foaming and expansion at 1190-1280°C, rapid cooling at 1280-680°C, medium-speed cooling at 680-280°C and slow cooling at 280-55°C.

[0081] In the preheating and drying stage, the temperature rise rate is 50℃ / min; in the oxidation and decomposition stage, the temperature rise rate is 30℃ / min; in the rapid cooling stage, the temperature drop rate is 90℃ / min; in the medium-speed cooling stage, the temperature drop rate is 45℃ / min; in the slow cooling stage, the temperature drop rate is 20℃ / min.

[0082] Comparative Example 1

[0083] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 1 is different from that in embodiment 1 in that the composition of the brick blank does not contain high white ball clay and medium white ball clay.

[0084] Comparative Example 2

[0085] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 2 is different from that in example 1 in that the composition of the brick blank does not contain bentonite.

[0086] Comparative Example 3

[0087] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 3 is different from that in example 1 in that in step S2, the moisture content of the powder is controlled at 8%.

[0088] Comparative Example 4

[0089] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 4 is different from that in example 1 in that in step S6, the surface of the pattern layer is wetted by spraying water at 24 g / m2.

[0090] Comparative Example 5

[0091] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 5 is different from that in example 1 in that the composition of the base glaze replaces the modified kaolin with kaolin.

[0092] Comparative Example 6

[0093] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 6 is different from that in example 1 in that the composition of the base glaze does not contain nepheline.

[0094] Comparative Example 7

[0095] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 7 is different from that in example 1 in that the composition of the surface glaze does not contain ultra-white zirconium silicate.

[0096] Comparative Example 8

[0097] The method for preparing the ultra-white diamond glazed tile with reduced crack defects in comparative example 8 is different from that in example 1 in that in step S7, the temperature rise rate of the brick blank to the firing temperature is 30°C / min.

[0098] The following experiments are conducted on the above-mentioned embodiments 1-2 and comparative examples 1-8 to verify or understand their performance. In the ultra-white diamond glazed tiles with reduced crack defects prepared in the above-mentioned embodiments 1-2 and comparative examples 1-8.

[0099]

[0100]

[0101] Table 1 Performance test comparison of ultra-white diamond glazed tiles with reduced crack defects in various embodiments and comparative examples

[0102] According to the above Table 1, it can be known that the ultra-white diamond glazed tiles with reduced crack defects prepared in Example 1 and Example 2, the high white ball clay and the medium white ball clay can fill the tiny gaps and defects in the brick blank, making the brick blank more dense and uniform, thereby reducing the shrinkage and deformation of the brick blank during the sintering process, and reducing the risk of edge cracks and cracks in the brick blank; bentonite can increase the plasticity and plasticity of the brick blank, making it easier to shape and maintain its shape, and not easy to crack; the modified kaolin component of the base glaze can increase the viscosity and adhesion of the base glaze, and improve the adhesion and coverage of the base glaze; in the top glaze, the ultra-white zirconium silicate, as a high-purity silicate mineral, has very high whiteness and gloss. The ultra-white zirconium silicate can increase the gloss and transparency of the top glaze, making it more beautiful, and can also improve the adhesion and wear resistance of the top glaze, reduce the stress concentration on the surface of the brick blank, thereby reducing the risk of edge cracks and cracks;

[0103] In Comparative Example 1, high white ball clay and medium white ball clay are used as fillers and reinforcing agents. They have fine particles and high plasticity, and can fill tiny gaps and defects in the bricks, making the bricks denser and more uniform, thereby reducing the shrinkage and deformation of the bricks during the sintering process, and reducing the risk of edge cracks and core cracks in the bricks.

[0104] In Comparative Example 2, bentonite has high water absorption and expansion properties, and can expand into a colloidal substance when in contact with water. During the preparation of the brick, bentonite can increase the plasticity and plasticity of the brick, making it easier to shape and maintain the shape, and avoid cracking;

[0105] In Comparative Example 3, the appropriate moisture content can provide fluidity and plasticity for the bricks during the preparation process. When the moisture content of the powder is moderate, it can flow and fill better in the mold, making the molding of the bricks more uniform and stable, so as to form a denser brick. In addition, during the mold pressing process, the moisture can act as a lubricant to better combine the powder particles and fill the pores, thereby improving the density and strength of the bricks, thereby reducing the risk of edge cracks and cracks in the center.

[0106] In Comparative Example 4, watering can make the surface of the pattern layer fully wet, increase the contact area between the glaze and the pattern layer, facilitate the uniform coverage and flow of the glaze, promote the adhesion of the glaze, and enable the glaze layer to better adhere to the pattern layer; while too little water may not be able to fully wet the surface of the pattern layer, resulting in insufficient or uneven adhesion of the glaze; too much water will cause the glaze to be overly diluted, the fluidity is too strong, and it is difficult to control the uniformity of glazing;

[0107] In Comparative Example 5, the modified kaolin can increase the viscosity and adhesion of the base glaze, improve the adhesion and coverage of the base glaze, and when the base glaze is attached to the surface of the brick, the viscosity of the modified kaolin can help the base glaze to better combine with the brick, thereby enhancing the structural stability of the brick;

[0108] In Comparative Example 6, the role of nepheline in the base glaze is to increase the fluidity and adhesion of the base glaze. When the base glaze flows to the surface of the brick, the nepheline can improve the meltability and wettability of the base glaze, making it easier to cover the surface of the brick and form a uniform structure.

[0109] In Comparative Example 7, ultra-white zirconium silicate, as a high-purity silicate mineral, has high whiteness and glossiness. In the glaze, ultra-white zirconium silicate can increase the gloss and transparency of the glaze, making it brighter, and can also improve the adhesion and wear resistance of the glaze, reduce stress concentration on the surface of the brick, and thus reduce the risk of edge cracks and cracks.

[0110] In comparative example 8, the firing stages of the brick blank in the roller kiln include: dehumidification at 170-280°C. During this stage, the temperature in the kiln gradually increases, which helps to evaporate and remove the moisture inside the brick blank. By gradually reducing the moisture content of the brick blank, the internal stress generated during the evaporation of moisture can be reduced; preheating and drying at 280-680°C. During this stage, the brick blank is further heated to remove residual moisture and volatile substances. Appropriate preheating and drying can make the temperature and humidity inside the brick blank evenly distributed, reducing the temperature and humidity gradient during the sintering process; oxidation decomposition at 68 0-1200℃, at this stage, the organic matter in the brick begins to oxidize and decompose, releasing gases and other volatile substances. This process helps stabilize the structure of the brick and reduce the accumulation of internal stress; vitrification firing 1200℃, at this stage, the brick gradually reaches the vitrification temperature, and the brick particles begin to melt and combine, which helps to further enhance the structural stability of the brick and reduce the generation of internal stress; foaming expansion 1200-1280℃, at this stage, the gas in the brick begins to expand, forming pores and pores, which helps to release internal stress. Reduce the internal pressure of the brick; rapid cooling 1280-680℃, medium cooling 680-280℃ and slow cooling 280-55℃, cooling in different temperature ranges, including rapid cooling, medium cooling and slow cooling. The appropriate cooling process can control the temperature reduction rate of the brick to avoid thermal stress caused by too fast cooling; through the above firing stage settings, the temperature and humidity changes of the brick can be controlled, thereby gradually releasing the internal stress and reducing the risk of edge cracking and core cracking; in the preheating and drying stage, the temperature rise rate is 40℃ / min; in the oxidation decomposition stage, the temperature rise rate is 30℃ / min; in the rapid cooling stage, the temperature drop rate is 80℃ / min; in the medium-speed cooling stage, the temperature drop rate is 35℃ / min; in the slow cooling stage, the temperature drop rate is 15℃ / min; in the preheating and drying stage, the moisture in the brick needs to be evaporated and removed, and a faster temperature rise rate helps to quickly heat the brick to a higher temperature and promote the evaporation and removal of moisture; in the oxidation decomposition stage, the organic matter in the brick begins to oxidize and decompose, releasing gas and other volatile substances. A slower temperature rise rate helps to control the decomposition and oxidation reactions of organic matter, avoid the rapid release of gases and volatile substances caused by too fast a temperature rise rate, and reduce the accumulation of internal stress; in the cooling stage, an appropriate temperature drop rate helps to control the temperature drop rate of the bricks and avoid thermal stress caused by too fast cooling; specifically, the faster temperature drop rate in the rapid cooling stage helps to quickly cool the bricks to a lower temperature and avoid the generation of excessive thermal stress in the bricks; the moderate temperature drop rate in the medium-speed cooling stage helps to further stabilize the temperature and structure of the bricks; the slower temperature drop rate in the slow cooling stage can gradually cool the bricks, reduce the temperature gradient, and help to further release internal stress.

[0111] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing ultra-white diamond glazed tiles with reduced crack defects, characterized in that: The following steps are involved: S1. Mix the raw materials of the bricks according to a certain weight ratio to obtain a mixed raw material; then put the mixed raw material into a ball mill for ball milling; control the moisture content to 33-36%, the fineness to 0.6-0.8%, the specific gravity to 1.55-1.65 g / ml, and the flow rate to 35-65 s to obtain a ball mill slurry; The brick blank is composed of the following components by weight: potassium sodium sand: 40-55 parts, potassium sand: 10-15 parts, high white ball clay: 3-5 parts, medium white ball clay: 14-20 parts, bentonite: 4-8 parts, superplastic clay: 5-8 parts, bauxite: 1-2 parts, black clay: 0-2 parts, talcum particles: 2-4 parts, brightener: 0.2-1 parts, debonding agent: 0.4-0.8 parts, water glass: 0.3-0.7 parts, and reinforcing agent 0.1-0.3 parts; S2, the ball mill slurry is filtered through an 80-mesh sieve to filter out coarse particles and wood residue impurities, and then iron is removed, and then the ball mill slurry is pressurized to be atomized into droplets, and then spray dried into powder; wherein the moisture content of the powder is controlled at 7-7.5%, and the particle size distribution is: 40-mesh sieve upper material> 68%, 100-mesh sieve lower material< 5%; S3, applying the powder to a mold to obtain a green body, and pressing the green body through a press to obtain a brick body, wherein the thickness of the brick body is 11.5-12 mm; S4, placing the bricks in a drying kiln and drying them at 140-250°C to make the moisture content in the bricks less than 0.7% of the total mass; S5. The dried bricks are glazed with a bell glaze sprayer, and the glaze amount is 110-120g / m 2 , to obtain the base glaze layer; The base glaze is composed of the following components by weight: potassium feldspar: 15-20 parts, sodium feldspar: 24-32 parts, silica sand powder: 38-42 parts, modified kaolin: 12-14 parts, calcined talc: 12-16 parts, nepheline: 4-12 parts and aluminum oxide: 2-3 parts; S6, inkjet printing is performed on the surface of the base glaze layer to obtain a pattern layer, and then after drying at 85-95°C, the surface of the pattern layer is coated with a 12-18g / m 2 Wet with water, then press 170-200g / m 2 applying a top glaze to obtain a top glaze layer; The glaze is composed of the following components by weight: white stone powder: 30-38 parts, ultra-white zirconium silicate: 8-12 parts, calcite: 4-8 parts, calcite: 22-26 parts, quartz: 4-6 parts, aluminum oxide: 1-2 parts and titanium oxide: 0.1-0.6 parts; S7. Place the bricks prepared in step S6 into a drying kiln for drying at a drying temperature of 170°C. Control the moisture content of the bricks in the drying kiln to be 0.3%. Then send them into a roller kiln for firing at a firing temperature of 1190-1230°C for 50-60 minutes to obtain ultra-white diamond glazed tiles with reduced crack defects, which are provided with a brick, a base glaze layer, a pattern layer and a surface glaze layer from bottom to top.

2. The method for preparing ultra-white diamond glazed tiles with reduced crack defects according to claim 1, characterized in that: In step S1, during the ball milling process, 1.2 wt% sodium tripolyphosphate and 0.7 wt% carboxymethyl cellulose are added to the mixed raw materials for co-ball milling, and the ball milling time is 4-8 hours.

3. The method for preparing the ultra-white diamond glazed tile with reduced crack center defects according to claim 1, characterized in that: The preparation process of the modified kaolin is as follows: kaolin, triethanolamine, solvent water and urea are added into a ball mill in a mass ratio of 14:3:36:5 for ball milling for 20-40 minutes, the ball milling speed is 400-480r / min, the slurry is left to stand for 24 hours after being milled, and then dehydrated and dried for standby use.

4. The method for preparing the ultra-white diamond glazed tile with reduced crack center defects according to claim 1, characterized in that: In step S3, the pressure of the press is 2800 KN, and the thickness of the green body is controlled to be 13-14 mm.

5. The method for preparing ultra-white diamond glazed tiles with reduced crack defects according to claim 1, characterized in that: In step S7, the firing stages of the bricks in the roller kiln include: dehumidification at 170-280°C, preheating and drying at 280-680°C, oxidation decomposition at 680-1190°C, vitrification firing at 1190-1230°C, foaming and expansion at 1230-1280°C, rapid cooling at 1280-680°C, medium-speed cooling at 680-280°C and slow cooling at 280-55°C.

6. The method for preparing ultra-white diamond glazed tiles with reduced crack defects according to claim 5, characterized in that: In the preheating and drying stage, the temperature rise rate is 40-50℃ / min; in the oxidation and decomposition stage, the temperature rise rate is 20-30℃ / min; in the rapid cooling stage, the temperature drop rate is 80-90℃ / min; in the medium-speed cooling stage, the temperature drop rate is 35-45℃ / min; in the slow cooling stage, the temperature drop rate is 15-20℃ / min.

7. An ultra-white diamond glazed tile with reduced crack defects, characterized in that: The ultra-white diamond glazed tile is prepared by the method for preparing the ultra-white diamond glazed tile with reduced crack defects as described in any one of claims 1 to 6.

Citation Information

Patent Citations

  • Super-wear-resistant marble tile formula and production process

    CN110104952A

  • Spot archaized brick and preparation method thereof

    CN110526744A